SOME ISSUES OF STANDARDIZATION OF GEOGRAPHICAL NAMES - Seytniyazov K. M. (Bright Mind Publishing, 2025)
Toponyms are of great importance in teaching geography. On national and international standardization of geographical names. The role of coordinating the work of organizations involved in the standardization of geographical names in different countries and their dissemination among UN member states. Tasks requiring research into the physical and geographical aspects of toponyms, substantiation of the rule of natural features of a place in the naming and renaming of geographical objects, creation of a card index and a register of geographical names.
Keywords: Toponyms, standardization, classification, geographical names, geographical objects, terms, transliteration.